Historical pattern archive womens's clothing 1837-1969 - Bernard, Thomas John ca. 20. Jh; Linton, Marcy ca. 20. Jh (Routledge, 2020)
"Historical Pattern Archive: Women's Clothing 1837-1969 is the first book of its kind to capture such a wide range of women's period patterns in one book, featuring 83 patterns spanning over a century of clothing. The book offers an accurate pattern of each garment on a 1/8" graph that can be used to scale the pattern up to its original size, drawings of each piece from multiple angles, and instructions about how the original garment was constructed and what materials were used. Capturing research and information about garments that would have otherwise stayed hidden or disappeared permanently due to age, wear, or poor storage conditions, this volume is designed to be a tool to preserve history through documenting vintage clothing. Written for historians, reenactors, costumer makers, and costume designers, Historical Pattern Archive will enable readers to study the history behind each piece, implement their original techniques, and recreate unique garments that are both beautiful and historically accurate"--
Keywords: Geschichte 1837-1969; Frauenkleidung; Schnittmuster; Frau; Kleidung; Dressmaking / Patterns; Costume; Women's clothing / History; Dressmaking; Women's clothing; History; Patterns